2021
DOI: 10.1111/acem.14366
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a rapid glial fibrillary acidic protein/ubiquitin carboxyl‐terminal hydrolase L1 test for the prediction of intracranial injuries on head computed tomography after mild traumatic brain injury

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 37 publications
1
22
0
2
Order By: Relevance
“…It was suggested that GFAP levels in plasma reflect amyloid-b pathology better than CSF levels as only plasma GFAP could differentiate between amyloid-b positive and negative CN individuals 15 . However, it is also clear that increased plasma GFAP may not only be present in AD, as astrocytosis occurs in response to many different pathological processes in the CNS 46 , and increased plasma GFAP levels have also been linked with conditions such as traumatic brain injury, stroke, FTD, and multiple sclerosis 44,[47][48][49] . It remains to be determined how plasma GFAP can be utilized in AD, but it can be speculated that its early and gradual increase together with its association with amyloid-b pathology would make it useful for predicting and following disease progression both in clinical practice and during clinical trials, as well as to support inclusion of individuals with early AD 50 .…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that GFAP levels in plasma reflect amyloid-b pathology better than CSF levels as only plasma GFAP could differentiate between amyloid-b positive and negative CN individuals 15 . However, it is also clear that increased plasma GFAP may not only be present in AD, as astrocytosis occurs in response to many different pathological processes in the CNS 46 , and increased plasma GFAP levels have also been linked with conditions such as traumatic brain injury, stroke, FTD, and multiple sclerosis 44,[47][48][49] . It remains to be determined how plasma GFAP can be utilized in AD, but it can be speculated that its early and gradual increase together with its association with amyloid-b pathology would make it useful for predicting and following disease progression both in clinical practice and during clinical trials, as well as to support inclusion of individuals with early AD 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the company Abbott Laboratories (Chicago, IL USA) has developed the FDA approved Abbott's i-STAT™ Alinity™ handheld device which can produce UCHL1 results within 15 min after a plasma sample has been inserted. This technology has been shown to have good sensitivity in predicting acute traumatic intracranial injury 14 . All these advancements make the investigation of UCHL1 as a biomarker that may aid in SRC diagnosis quite lucrative.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these features, notably PTA, typically rely on subjective self-report. Recently, the blood-based biomarker, GFAP (a marker of astrocytic response to injury), has been identified as having clinical utility in evaluation of mTBI [ 16 ], a diagnosis which historically has also relied upon subjective symptom reporting and clinical judgement. It is therefore plausible that blood-based biomarkers could similarly be used to predict post-TBI mental health outcomes such as PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Banyan Biomarkers; 2018; i-STAT TBI Plasma Cartridge. Abbott Point of Care Inc. Abbott Park, IL; 2020) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%